Pembelajaran Sosiologi Secara Daring Selama Pandemi COVID-19 di SMA N 1 Taebenu Nusa Tenggara Timur - Syahrul, Syahrul; Yusuf, Nur Wahida; Yayuk Julyyanti; Nautu, Albert K.; Arifin (Jurnal Penelitian dan Pendidikan IPS, 2023)
This study aims to find out about online sociology learning during the COVID-19pandemic at SMA N 1 Taebenu. This research was qualitative research that was intended todeeply understand the effectiveness of online sociology learning during the COVID-19pandemic. The subjects of this study were students, teachers, and the headmaster. The datacollection used observation, interviews, and documentation. Interactive analysis techniquesinclude data reduction, data display, and drawing conclusions. The results of research thatimplementing online learning during the COVID-19 pandemic was not effective because inthe learning process students and teachers experienced obstacles by teachers experiencinglimitations in the use of learning platform (technology). Then the obstacles experienced bystudents were their limitations in facilities such as not having a cellphone, laptop, also nothaving an internet package, and being constrained by the internet connection